Marx, the labour theory of value and the transformation problem - Burns, Tony (SAGE Publications, 2016)
This article reconsiders what Marx says about the transformation problem in Chapter IX of Capital Volume III, in the light of Marx's claim, made in Capital Volume I, that the value of a commodity is determined by the socially necessary labour time that goes into its production. The article criticises the traditional way of thinking about the transformation problem, according to which what Marx is doing in Chapter IX is considering the transformation of values into prices ('prices of production'). I argue that Marx's prices of production may be thought of as modified values. The discussion in Chapter IX is usually seen as a supplement to the labour theory of value. On this view its purpose is to explain how and why the prices of commodities sometimes deviate from their values. Against this view, the paper argues that Marx's remarks in Chapter IX can be seen as an elaboration on or development of the labour theory of value. It is a refinement of the account offered in Capital Volume I, which takes into consideration what Marx had in mind there when he introduced the notion of socially necessary as opposed to actual labour-time. The paper draws attention to the importance of Marx's distinction between the individual value of a commodity (determined by actual labour-time) and its social value (determined by socially necessary labour-time). It also draws attention to the methodological difficulties that are generated by any attempt to read Marx in this way.